2016
DOI: 10.1093/mnras/stw386
|View full text |Cite
|
Sign up to set email alerts
|

On the migration of three planets in a protoplanetary disc and the formation of chains of mean motion resonances

Abstract: We study the migration of three-planet systems in an irradiated 1+1D α-disc with photoevaporation. We performed 2700 simulations with various planets' masses and initial orbits. We found that most of the systems which ended up as compact configurations form chains of mean motion resonances (MMRs) of the first and higher orders. Most of the systems involved in chains of MMRs are periodic configurations. The period ratios of such system, though, are not necessarily close to exact commensurability. If a given sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 44 publications
(59 reference statements)
2
20
0
Order By: Relevance
“…the planets to migrate. However, orbital migration may not be convergent (Migaszewski 2015(Migaszewski , 2016, that is, not leading to resonant capture. Moreover, some mechanisms have been proposed to inhibit the capture even in the case of convergent migration, such as turbulence in the disk or e-dependent migration rates.…”
Section: Discussionmentioning
confidence: 99%
“…the planets to migrate. However, orbital migration may not be convergent (Migaszewski 2015(Migaszewski , 2016, that is, not leading to resonant capture. Moreover, some mechanisms have been proposed to inhibit the capture even in the case of convergent migration, such as turbulence in the disk or e-dependent migration rates.…”
Section: Discussionmentioning
confidence: 99%
“…The curve corresponds to the Laplace three-body resonance, for which the mean motions of the planets obey the relation n 1 − 3 n 2 + 2 n 3 = 0. A three-planet system that is initially involved in this chain of MMRs would evolve divergently along a curve y −1 = 3/2 − x/2, where x ≡ P 2 /P 1 = n 1 /n 2 and y ≡ P 3 /P 2 = n 2 /n 3 (Migaszewski 2016). We can see that even though τ 1 > τ 2 , P 2 /P 1 increases and the observed configuration is omitted.…”
Section: Formation Of the Kepler-30 Systemmentioning
confidence: 93%
“…Slowing down the migration of this planet does not necessarily lead to an increase of P 3 /P 2 without changing P 2 /P 1 . The divergent migration of three planets away from a given chain of MMRs can occur along certain paths at the period ratio-period ratio diagram (Migaszewski 2016). It is then possible that P 2 /P 1 would also increase, even though τ 1 > τ 2 .…”
Section: Formation Of the Kepler-30 Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Migaszewski (2015Migaszewski ( , 2016 studied the effect of more complex disk models on migration of planetary pairs, including photo-evaporation and different opacity laws. They found that several regions of divergent migration appear in the disk that may lead to departure from exact resonance and even ejection from the commensurabilities.…”
Section: Introductionmentioning
confidence: 99%